2014
DOI: 10.1111/tid.12301
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical characteristics, and outcome of invasive aspergillosis in renal transplant patients

Abstract: While classical risk factors described for IA in liver recipients are still valid, IA appears later in renal patients and is commonly associated with co-morbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
4
21
1
5
Order By: Relevance
“…3,10 Thus, despite an increase in transplants among elderly and highly immunized patients, no IA breakthrough was observed. Although early IA was described in half of the IA cases in solid organ transplantation (SOT) 10 years ago, 3,11 our study, in accordance with other recent studies, 4,6 demonstrated that late IA (>6 months after transplantation) is more frequent in KTR, occurring in 69% of patients.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…3,10 Thus, despite an increase in transplants among elderly and highly immunized patients, no IA breakthrough was observed. Although early IA was described in half of the IA cases in solid organ transplantation (SOT) 10 years ago, 3,11 our study, in accordance with other recent studies, 4,6 demonstrated that late IA (>6 months after transplantation) is more frequent in KTR, occurring in 69% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the global mortality rate was still high: the overall mortality rate was 56.3% (9 of 16 patients) compared with 70% in 2 retrospective studies without voriconazole. 3,4 However, the 12-week mortality rate was lower than that reported in other studies of patients receiving voriconazole (ie, 6% in our study compared to 19% in the recent study of Heylen et al 6 and 34.4% among SOT recipients. 7 Similarly, in the Veroux et al 10 study, none of 4 patients receiving voriconazole died within 13 months after IA.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations